Surgical Repair of Nasal Septal Perforation by Mucosal Rotational Flap and Interposition of Cryopreserved Amniotic Membrane - Farrokh Farhadi Shabestari; Reza Khorshidi Khiavi; Mohsen Hashemi; Tannaz Abdollahzadeh Baghei (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The surgical repair of nasal septal perforation (NSP) has always been a challenging procedure and no consensus has been made about a definitive protocol.Purpose: In the current study, we investigated the use of cryopreserved amniotic membrane with mucosal rotational flap for the surgical repair of NSPs.Materials and Method: In this prospective clinical study, 12 patients with symptomatic NSP underwent primary surgical repair, between December 2018 and October 2019. The surgical procedure comprised of a rotational flap on one side of the defect and cryopreserved amniotic membrane as an interpositional graft in the mucoperichondrial pocket on the other side. The patency of defect was checked at a follow-up appointment at least 3 months after surgery.Results: Successful repair was perceived in 10 of 12 (83%) of patients. Reperforation occurred in two patients but the size of the defect was smaller than the original one. All of the patients reported elimination of all symptoms associated with NSP.Conclusion: The use of cryopreserved amniotic membrane as an interpositional graft accompanied by a mucosal rotational flap seems to be efficient in alleviating the symptoms of NSP and closure of the defect.